(untitled) (Plant Tissue Culture and Biotechnology, 2016)
Glinus lotoides L. is a valuable medicinal herb for the treatment of human and livestock ailments. However, it was listed under endangered plant species due to over utilization and lower seed viability. The purpose of this study has been to develop a micropropagation method from nodal segments of G. lotoides. MS containing various concentrations of Kn was used for culture induction. Best culture establishment (95%) and highest mean shoot number (2.45 ± 0.37) were achieved on a medium containing 1.5 mg/l Kn. Even though different concentrations of 6?benzyl aminopurine (BAP), Kn and ??naphthalene acetic acid (NAA) were utilized for shoot proliferation, the highest number of shoots per nodal segment (3.66 ± 0.61) was attained in the medium containing 1.0 mg/l BAP in combination with 0.2 mg/l NAA. Shoots were rooted on half strength MS containing IBA, IAA and NAA. In a medium containing 1.5 mg/l IBA, 5.80 ± 1.10 roots per shoot, 1.05 ± 0.10 cm root length and 100% root generation frequency were obtained. Plantlets were successfully established under greenhouse conditions with 94% survival rate and no aberrant plants were detected. Plant Tissue Cult. & Biotech. 26(1): 131-141, 2016 (June)